Associations between sugar-sweetened beverages consumption, duration of physical exercise, and depressive symptoms among Tibetan university students at high altitude - Yang, Yang; Liu, Jia; Dai, Duo (Frontiers in Psychology, 2024)
Background Depressive symptoms have become a public health issue of common concern in countries all over the world, and have many negative impacts on university students’ study and life. Depressive symptoms are influenced by many factors, including sugar-sweetened beverages (SSBs) consumption and duration of physical activity. However, no study has been conducted on the association between sugar-sweetened beverage consumption, duration of physical exercise, and depressive symptoms among Tibetan university students at high altitudes. Methods In this study, a self-assessment survey of SSBs consumption, duration of physical exercise, and depressive symptoms was conducted on 6,259 (2,745 boys, 43.86%) Tibetan university students aged 19–22 years in Lhasa and Ganzi areas, China, using stratified whole population sampling. The associations were also analyzed using one-way analysis of variance, binary logistic regression analysis, and ordered logistic regression analysis in the generalised linear model. Results The proportions of mild depression symptoms, moderate depression symptoms, and major depressive symptoms among Tibetan boys university students in high-altitude areas of China were 18.0, 22.9, and 1.5%, respectively; the proportions of girls students were 20.1, 21.9, and 1.5%, respectively, 1.5%, and the differences in the detection rates of depressive symptoms between sex were statistically significant (χ2 value = 14.253, p < 0.01). Ordered logistic regression analyses showed that using duration of physical exercise >60 min/d and SSBs ≤1 times/week as the reference group, the duration of physical exercise <30 min/d and SSBs ≥5 times/week groups had the highest risk of developing depressive symptoms was the highest risk (OR = 6.98, 95% CI: 5.05–9.65; p < 0.001). Conclusion This study confirmed that there was a positive association between SSBs consumption and depressive symptoms and a negative association between the duration of physical exercise and depressive symptoms among Tibetan university students at high altitudes in China. In the future, SSBs consumption should be effectively controlled and the duration of physical exercise should be increased to reduce the occurrence of depressive symptoms and promote the physical and mental health of Tibetan university students in high-altitude areas.